Benefits of meeting nutrient reduction targets for the Baltic Sea : a contingent valuation study in the nine coastal states - Ahtiainen, Heini; Artell, Janne; Czajkowski, Mikolaj; Hasler, Berit; Hasselström, Linus; Huhtala, Anni; meyerhoff, Jurgen; Smart, James C.R.; Söderqvist, Tore; Alemu, Mohammed H.; Angeli, Daija; Dahlbo, Kim; et al. (Taylor & Francis, 2014)
This paper presents the results of an internationally coordinated contingent valuation study on the benefits of reducing marine eutrophication in the Baltic Sea according to current policy targets. With over 10,500 respondents from the nine coastal states around the sea, we examine public willingness to pay (WTP) for reduced eutrophication and its determinants. There are considerable differences in mean WTP between countries, with Swedes being willing to pay the most and Latvians the least. The aggregate annual WTP is approximately €3600 million. In addition, we find that countries are heterogeneous in terms of the effects of income, attitudes and familiarity on WTP. Income elasticities of WTP are below 1 for all countries, ranging between 0.1 and 0.5. Attitudes and personal experience of eutrophication are important determinants of WTP, but the specific effects differ between countries. The findings can be used in economic analyses for the European Union (EU) Marine Strategy Framework Directive and to justify additional eutrophication reduction measures in the Baltic Sea.
Keywords: Maatalous - yleistä, maatalousekonomia,maatalousneuvonta, maaseudun kehittäminen; willingness to pay; Baltic Sea; Itämeri; eutrophication; contingent valuation; water quality